2008
DOI: 10.1021/jp7101644
|View full text |Cite
|
Sign up to set email alerts
|

Charge Transfer across Self-Assembled Nanoscale Metal−Insulator−Metal Heterostructures

Abstract: The kinetics of charge transfer across a metal−insulator−metal architecture is investigated by electrochemical impedance spectroscopy. The insulating component of the architecture is composed by a self-assembled monolayer of 11-mercaptoundecanoic acid (MUA), polyelectrolyte multilayers, and a monolayer of 22 nm SiO2 nanoparticles. The charge transfer to the hexacyanoferrate couple is strongly hindered by the MUA monolayer. The blocking properties effectively vanish with the adsorption of a diluted monolayer of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
59
1
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(69 citation statements)
references
References 14 publications
6
59
1
2
Order By: Relevance
“…This implies that the resistance of each BPT molecule is far below the quantum conductance, as previously suggested 17 . However this disagrees with [19][20][21][22].…”
mentioning
confidence: 78%
“…This implies that the resistance of each BPT molecule is far below the quantum conductance, as previously suggested 17 . However this disagrees with [19][20][21][22].…”
mentioning
confidence: 78%
“…However, as this system already challenges expectations the question needs to be answered. It has been answered to some extent by Fermin (where the phenomenon was also observed when silica nanoparticles were present between the electrode and the metal nanoparticles [16] ), by our group (where the underlying electrode is silicon and any direct contact of the nanoparticles to the silicon electrode would cause oxidation of the silicon surface which is not observed [20] ), and by Shapter and co-workers with carbon nanotubes attached to silicon electrodes with an intervening oxide layer . [21] However, all these cases are somewhat different to nanoparticles contacting an alkanethiol SAM.…”
mentioning
confidence: 95%
“…[13] In a very elegant series of papers, Fermin and co-workers explored the electrochemistry of electrode-SAM-NP assemblies in considerable detail. [8,[16][17][18] The construct employed involved an alkanethiol modified gold electrode, where the alkanethiol possessed a carboxylic acid at its distal end. To bind gold nanoparticles to this surface, a poly-l-lysine was adsorbed onto the SAM, with the amines of this weak polyelectrolyte serving as coupling points to which gold nanoparticles were bound.…”
mentioning
confidence: 99%
“…This interest has been heightened by recent observations that electron transfer across the organic layer in electrode-organic layer-nanoparticle constructs can be very efficient. In fact studies by us [2] and Fermin and co-workers [3] have shown that for self-assembled monolayers ranging in length between 3 and 11 carbons, the rate of electron transfer appears to be independent of the thickness of the otherwise insulating organic layer. This, somewhat unexpected observation, was very recently explained theoretically by Chazalviel and Allongue [4].…”
Section: Introductionmentioning
confidence: 99%